Ethnographies of Power: a political anthropology of energy - Loloum, Tristan; Abram, Simone; Ortar, Nathalie (Berghahn Books, 2024)
Energy related infrastructures are crucial to political organization. They shape the contours of states and international bodies, as well as corporations and communities, framing their material existence and their fears and idealisations of the future. Ethnographies of Power brings together ethnographic studies of contemporary entanglements of energy and political power. Revisiting classic anthropological notions of power, it asks how changing energy related infrastructures are implicated in the consolidation, extension or subversion of contemporary political regimes and discovers what they tell us about politics today.